The Effectiveness of Computerized Cognitive Training Combined With Whole Body Cryotherapy in Improving Cognitive Functions in Older Adults. A Case Control Study - Senczyszyn, Adrianna; Wallner, Renata; Szczesniak, Dorota Maria; Łuc, Mateusz; Rymaszewska, Joanna (Frontiers in Psychiatry, 2021)
Objectives: Subjective Cognitive Decline (SCD) and Mild Cognitive Impairment (MCI) are common in elderly population, and constitute a high-risk group for progression to dementia. Innovative, complex and engaging non-pharmacological methods of cognitive stimulation, implementable at this stage, are needed. The aim of the study was to determine the effect of Computerized Cognitive Training (CCT) combined with Whole Body Stimulation (WBC) on cognitive functions of cognitively normal and impaired (MCI) older adults. Methods: A 9-week single-blind pre/post case control trial was conducted. The study enrolled 84 adults aged 60 or older, allocated to one of two intervention groups: EG; CCT with psychoeducation, EG2; CCT with psychoeducation and 10 WBC sessions, or the control group (CG), which comprised patients receiving usual care. The primary outcome measures were cognitive functions evaluated with MoCA scale and several other neuropsychological tools. Depressive symptoms assessed with the GDS scale constituted the secondary outcome measures. Results: The results show evidence for increased performance in the assessment of general cognitive functioning in both EGs (p≤0.05). Significant improvement was also visible in several cognitive domains, such as verbal fluency (EG1&EG2), learning ability and immediate memory (EG1&EG2), delayed memory (EG2), attentional control (EG1) and information processing (EG2) (p≤0.05). However, only in the group with combined interventions (CCT+WBC) the participants presented significantly less depressive symptoms (p≤0.05). Conclusions: The results of the study suggest that CCT, especially in combination with WBC, might be a practical and effective method of improving cognitive performance. Moreover, this combination leads to a reduction of depressive symptoms.